EVALUATION OF THE EFFICIENCY OF WASTE SORTING BY WASTE PICKERS AT THE FINAL PROCESSING SITE TPA SARI MUKTI - Sri Murda Niati; Idha Silviyati; Endang Supraptiah; Gemala Cahya (UPT Publication and Journal Management, Islamic University of Kalimantan, 2024)
At the Sari Mukti Landfill, the reduction in the volume of waste entering the final processing is achieved through landfill management, composting, and sorting. The sorting that has been carried out so far is done by scavengers. Based on data and studies conducted at the landfill, it was concluded that the sorting efficiency, on average, between January and February is 0.81%. This efficiency of 0.81% was obtained from sorting in 5% of zones B and C, with a total of 385 scavengers. If we apply the same efficiency to 100% of the area, the number of scavengers required would be 7,700. However, the results of the study do not recommend increasing the number of scavengers. Instead, it is recommended to sort waste at the source. With the sorting mechanisms outlined in the discussion, it is hoped that only a small portion of organic waste will enter the landfill.